Mitochondrial 16S rRNA Characterization of Heterotrigona itama Colonies from Central Lampung, Indonesia - Priyambodo Priyambodo; Aditya Fahrezi; Elly Lestari Rustiati; Enny Saswiyanti; Eko Agus Srihanto; Aulia Imtitsal; Dian Neli Pratiwi; Nindy Permatasari (Biology, Medicine, & Natural Product Chemistry, 2026)
Stingless bees play important ecological and economic roles in tropical ecosystems, yet molecular baseline data for many regions in Sumatra remain limited. This study aimed to characterize mitochondrial genetic variation of Heterotrigona itama colonies from Punggur Subdistrict, Central Lampung, Indonesia, using partial 16S rRNA sequences. Three managed colonies were analyzed through PCR amplification and Sanger sequencing, followed by sequence alignment, BLAST comparison, genetic distance estimation using the Kimura-2-Parameter model, and phylogenetic reconstruction. All samples produced consistent amplicons of approximately 500 bp and showed complete nucleotide identity, indicating a single mitochondrial haplotype among the analyzed colonies. BLAST results revealed high similarity (96.91–98.38%) with reference sequences of H. itama. Genetic distance analysis showed zero divergence among the sampled colonies and low divergence (0.0069–0.0182) relative to other H. itama sequences, while higher divergence was observed with related taxa. Phylogenetic analysis placed all samples within a well-supported H. itama clade. These findings indicate mitochondrial uniformity among the sampled colonies and provide a preliminary genetic baseline for H. itama in Central Lampung. However, broader conclusions on population structure require further studies with larger sample sizes and additional molecular markers.